2018
DOI: 10.4081/pmc.2018.200
|View full text |Cite
|
Sign up to set email alerts
|

Transient femoral nerve palsy in spica cast treatment for developmental dysplasia of the hip

Abstract: A 4 months and half female child come to our attention for congenital dislocation of the left hip, previously treated in another hospital with abduction bracing, without satisfactory results. After progressive longitudinal bilateral traction, closed reduction under general anesthesia was performed and a spica cast was applied in the so-called human position. The patients remained in the spica cast for 6 weeks and then the plaster cast was renewed in narcosis for another 6 weeks. Once the second cast has been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Furthermore, the cast has many complications, including joint stiffness, pressure sores, skin rashes, skin ulceration, and infection with a possibility to reach septic shock, transient femoral nerve palsy, and cast-saw injuries during removal. [12][13][14][15][16][17][18][19] Superior mesenteric artery syndrome has been reported as a complication in a 10-year-old girl after hip spica application. [20] Transportation in vehicles becomes a real burden and may become unsafe.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the cast has many complications, including joint stiffness, pressure sores, skin rashes, skin ulceration, and infection with a possibility to reach septic shock, transient femoral nerve palsy, and cast-saw injuries during removal. [12][13][14][15][16][17][18][19] Superior mesenteric artery syndrome has been reported as a complication in a 10-year-old girl after hip spica application. [20] Transportation in vehicles becomes a real burden and may become unsafe.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies evaluating the relationship between malocclusion and scoliosis described an increased prevalence of unilateral Angle Class II malocclusion, 17 an increased risk of crossbite 15 and left-right occlusal asymmetries 18 ; however, there was no agreement between the studies. 19 A recent systematic review concluded that there was no clear evidence of a causal relationship between spinal deformities and malocclusion and underlined the limited quality of the evidence available to support it. 20 Nevertheless, even though the results are not directly translatable to humans, three animal studies [21][22][23] showed the role of induced malocclusion on the irreversible degeneration of the spine, manifesting as scoliotic curves.…”
mentioning
confidence: 99%